Quantitative methods in business - Curnock, Audrey ([S.l.] : Nelson Thornes Ltd, 1996)
A step-by-step approach, allowing students to learn independently, building skills at their own pace;A practical, scenario-based approach which brings the subject to life, motivating students more effectively;Exercises with or without solutions, allowing either the lecturer or the student to monitor progress;Guidance on calculator and spreadsheet applications.
Keywords: Quantitative methods ,business